2005
DOI: 10.1038/sj.sc.3101871
|View full text |Cite
|
Sign up to set email alerts
|

Brown–Séquard-plus syndrome due to stab injury: a case report

Abstract: Study Design: Case report. Objective: To describe the mechanism of injury in this case and its clinical features. Magnetic resonance (MR) images of hemorrhage in spinal cord injury due to stab wound are discussed. Methods: We describe the case of a 21-year-old woman who was stabbed in the right side of her neck and developed left-sided Brown-Se´quard syndrome plus loss of bilateral proprioceptive sensation. Neither plain radiographs nor computed tomography of the cervical spine demonstrated any foreign bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…However, MRI does not clearly show the extent of interruption to the spinal cord tracts. Although the clinical presentation and the severity of the syndrome vary, the MRI findings are relatively same (8,9). However, in this report, we have shown that diffusion tensor tractography clearly demonstrates the interruption of long spinal cord tracts at the site of injury and the extent of transection of the spinal cord is depicted clearly.…”
Section: Discussionmentioning
confidence: 57%
“…However, MRI does not clearly show the extent of interruption to the spinal cord tracts. Although the clinical presentation and the severity of the syndrome vary, the MRI findings are relatively same (8,9). However, in this report, we have shown that diffusion tensor tractography clearly demonstrates the interruption of long spinal cord tracts at the site of injury and the extent of transection of the spinal cord is depicted clearly.…”
Section: Discussionmentioning
confidence: 57%
“…Clearly identified indications for immediate exploration are a retained foreign body, a persistent CSF leak, radiologic signs of extrinsic cord compression such as by hematoma, and sepsis due to the delayed development of an epidural abscess or granuloma. 2,3,8 The skin wound may be missed easily, as it is often small and not situated directly over the craniocervical junction. Therefore, it is important to correctly identify such a wound and to be aware of the associated symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…The most commonly reported site for a stab wound is in the thoracic spine, followed by the cervical spine and the lumbar spine. [1][2][3] Reports of stab injuries at the craniocervical junction are rare. [4][5][6] Because of the anatomy of this area, the penetrating weapon is deflected by the occipital squama into the atlanto-occipital or atlantoaxial interspace in the craniocervical junction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, spinal cord injuries (SCIs) make up only 2.6% [2] of all the trauma cases, of which fewer than 1.5% [3][4][5] can be attributed to stab wounds. The most reported site is the thoracic spine, followed by the cervical and the lumbar spine [3,6,7]. The craniocervical junction is rarely affected due to the anatomy of this region [8][9][10].…”
Section: Introductionmentioning
confidence: 99%